2015
DOI: 10.1002/rcm.7439
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a proton‐conducting ionic liquid on secondary ion formation in time‐of‐flight secondary ion mass spectrometry

Abstract: Since [dema][TfO] can act as a proton source, its primary beam can effectively generate protonated secondary ions of analytes. Consequently, proton-conducting ionic liquids such as [dema][TfO] are expected to have great potentials as primary ion beams in TOF-SIMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…To be more precise, we have used diethylmethylammonium trifluoromethanesulfonate ([dema][TfO]), which is a commercially available PIL, and demonstrated that a primary [dema][TfO] cluster ion beam was effective in protonating arginine . Since a [dema][TfO] molecule has an active proton, it is likely that its beam irradiation can promote proton transfer reactions to form secondary ions [M + H] + . However, the [dema][TfO] cluster beam was not effective in protonating polyethylene glycol …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To be more precise, we have used diethylmethylammonium trifluoromethanesulfonate ([dema][TfO]), which is a commercially available PIL, and demonstrated that a primary [dema][TfO] cluster ion beam was effective in protonating arginine . Since a [dema][TfO] molecule has an active proton, it is likely that its beam irradiation can promote proton transfer reactions to form secondary ions [M + H] + . However, the [dema][TfO] cluster beam was not effective in protonating polyethylene glycol …”
Section: Introductionmentioning
confidence: 99%
“…Since a [dema][TfO] molecule has an active proton, it is likely that its beam irradiation can promote proton transfer reactions to form secondary ions [M + H] + . However, the [dema][TfO] cluster beam was not effective in protonating polyethylene glycol …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…voltage, yet this generally implies low source brightness and a preferential formation of smaller droplets 129 . They also have utilized the ionic liquids as matrix-coating materials (enhances ionization and yields) to match the projectile types 129 .…”
Section: Figure 6 Schematic Of An Iontof Argon Gas Cluster Primary Imentioning
confidence: 99%
“…They also have utilized the ionic liquids as matrix-coating materials (enhances ionization and yields) to match the projectile types 129 . …”
Section: Figure 6 Schematic Of An Iontof Argon Gas Cluster Primary Imentioning
confidence: 99%